Development of an Integrated "Vein" Pop-Up Book Media for Science Number Patterns in Increasing Interest and Critical Thinking - Ria Budi Astuti; Helti Lygia Mampouw; Ferdy Semuel Rondonuwu (Jurnal Penelitian Pendidikan IPA, 2026)
Science learning in elementary school plays an important role in developing students’ learning interest and critical thinking skills. However, students often experience difficulties in understanding abstract concepts such as vertebrate and invertebrate classification due to limited interactive learning media. This study aimed to develop and evaluate the feasibility and effectiveness of an integrated learning medium called the “VEIN” (Vertebrate–Invertebrate) flashcards and 3D pop-up book to increase students’ learning interest and critical thinking skills. This research employed a Research and Development (R&D) design conducted in two elementary schools in Jambi City involving 16 third-grade students. Data were collected through observation, interviews, questionnaires, documentation, and critical thinking tests, and analyzed quantitatively using percentage analysis. The results showed that 62.5% of students were categorized as having high learning interest, 25% medium, and 12.5% low. Critical thinking skills improved particularly in interpretation (68.75%) and analysis (62.5%) indicators, while inference reached 43.75% in the medium category. These findings indicate that the VEIN media effectively promotes active engagement, facilitates concrete conceptual understanding, and supports the gradual development of critical thinking skills. In conclusion, the VEIN flashcards and pop-up book are feasible, practical, and effective as innovative media to enhance learning interest and critical thinking in integrated elementary science learning